Aksesibilitas Fasilitas Umum Fisik Bagi Penyandang Disabilitas Di Kota Bandung - Aulia Ananda Kartika; Wirman Syafri; Rizki Amalia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the accessibility of physical public facilities for persons with disabilities in Bandung City. Existing accessibility has not fully met the principles of convenience, usability, safety, and independence, thereby limiting the mobility and social participation of persons with disabilities. The research gap lies in the limited implementation of inclusive accessibility in physical public facilities. This study employs John Black’s Accessibility Theory, which consists of four dimensions: convenience, usability, safety, and independence. A qualitative descriptive approach was used, with data collected through interviews with seven informants, observations, and documentation. The findings indicate that, in terms of convenience, accessibility has not yet become a primary consideration in the development of public facilities. Regarding usability, the government tends to focus more on outputs, namely the availability of facilities, rather than outcomes such as convenience, usability, safety, and independence for persons with disabilities. In terms of safety, public facility safety systems have not been comprehensively integrated. Regarding independence, facility planning remains insufficiently inclusive, as it is still predominantly top-down and not fully based on users’ needs.